Flexible strain sensors with high sensitivity and large working range prepared from biaxially stretched carbon nanotubes/polyolefin elastomer nanocomposites. Issue 4 (14th November 2022) - Xiang, Dong; Chen, Xiaoyu; Li, Jiayi; Wu, Yuanpeng; Zhao, Chunxia; Li, Hui; Li, Zhenyu; Wang, Li; Wang, Ping; Li, Yuntao; Wang, Junjie
Abstract: Flexible strain sensors are a new generation of flexible and stretchable electronic devices that attracted increasing attention due to their practical applications in many fields. However, maintaining a wide detectable strain range while improving the sensitivity of flexible strain sensors remains challenging. In this study, flexible strain sensors with a large working range based on biaxially stretched carbon nanotubes (CNTs)/polyolefin elastomer (POE) nanocomposites were fabricated. Biaxial stretching was demonstrated to enhance the uniform dispersion and orientation of CNTs, thereby improving the performance of sensors. The optimal stretching ratios (SRs) of nanocomposites were investigated and the data revealed an increment in the sensitivity of sensors with SRs, while the working range first increased after biaxial stretching and decreased at higher SRs. Compared to the 9 wt% CNT/POE‐1.0 sensor with a gauge factor (GF) value of 2.37 and a detectable range of 0.5%–230%, the CNT/POE‐2.0 sensor exhibited an enhanced sensitivity (GF = 3935.12) coupled with a wider detectable range (0.5%–710%) and better stability. Besides, CNT/POE‐2.0 sensor also achieved the monitoring of head movements, mouth opening, facial expression, and physiological signals, showing a potential for use in wearable electronic products. Abstract : Flexible strain sensors with a large working range based on biaxially stretched carbon nanotubes (CNTs)/polyolefin elastomer (POE) nanocomposites were fabricated. Biaxial stretching was demonstrated to enhance the uniform dispersion and orientation of CNTs, thereby improving the performance of sensors. An increment in the sensitivity of sensors with SRs, while the working range first increased after biaxial stretching and decreased at higher SRs.